A cost‐efficient and simple protocol to enrich prey DNA from extractions of predatory arthropods for large‐scale gut content analysis by Illumina sequencing. Issue 1 (29th September 2016) - Krehenwinkel, Henrik; Kennedy, Susan; Pekár, Stano; Gillespie, Rosemary G.
Summary: Molecular analysis of predator gut content is a popular tool to uncover food web structure and has greatly profited from the emergence of next‐generation sequencing technology. However, the molecular recovery of prey spectra comes with many challenges, particularly the overabundance of predator DNA in extractions. When predator and prey are distantly related, predator‐specific blocking primers can be used to preferentially amplify prey DNA. But this is difficult in the case of arthropods, where prey and predator are often closely related. Here, we present a simple and cost‐efficient protocol for high‐throughput analysis of the gut content of predatory arthropods without the need for blocking primers. We test several factors for their potential to enrich prey DNA from extractions of predators, including size selection of DNA, selection of different body parts for extraction, and variation in extraction lysis time and PCR fragment length. Using a locally abundant spider species ( Hololena adnexa, Agelenidae), we show that prey DNA can be significantly enriched from predator extracts by selectively removing high molecular weight DNA and by extracting from the midgut and hindgut only. A comparison of our results with observational data from other agelenid spider species indicates a high efficiency of our approach. Our enrichment protocol allows for the parallel analysis of several hundred predators in a single MiSeq run, reducing the cost per specimen to only a few dollars and requiring a simple and minimal work flow. This will enable large‐scale and ecosystem‐wide analyses of niche differentiation and food web structure.